HYPOALBUMINEMIA: a hospital based study - P, Singh; S, Khan; A. H., Siddiqui (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Hypoalbuminemia occurs in a variety of disease states and is associated with an increased rate of complications during hospitalization, resulting in an increased length of stay. The purpose of this study is to investigate the prevalence of hypoalbuminemia in IPD and OPD patients and to see which age group and sex have high prevalence of hypoalbuminemia.Nine hundred forty four patients, attending Nepalgunj medical college and Teaching Hospital, Banke, Nepal from March 2011 to February 2012 were included in this study. The normal reference range for serum albumin was 3.5 – 5.5gm/dL in males and females. Hypoalbuminemia is defined as serum albumin < 3.5 gm/dL. The outcome assessments in the hypoalbuminemia and normal albumin groups were compared. Serum albumin level estimation was done by using the diagnostic reagent kit manufactured by RFCL kit , India. A number of 944 studies were selected, the statistical information of which was collected for systematic analysis.The results showed that the high prevalence of hypoalbuminemia found in males (89.72%) as compare to females(88.12%). The prevalence of hypoalbuminemia is different as the period of age and it increases after 21-40 years and high prevalence seen in after the age of 60. Serum albumin level was low in male as compare to female.